RESEARCH AND DEVELOPMENT IN COCONUT - K.V.A. Bavappa (International Coconut Community, 1986)
In the context of the fast reducing land‑to‑man ratio in the tropics, cropping systems which can integrate a variety of highly productive plant species and animals with human beings will have to be developed. Coconut having many favourable attributes is ideally suited for homestead farming under diverse situations. Its response to good management particularly fertilizer application and irrigation is indeed very good. Yield increases of the order of 84% due to manuring and 216% due to manuring and irrigation have been obtained in the native West Coast Tall. In coconut hybrids not only Wgher yields have been realised but better utilisation efficiency of native and applied nutrients observed, making them highly suited for improving the economic viability of small holdings. The potential that coconut offers for mixed cropping with a variety of crops, and mixed farming is very high. High density cropping in coconut plantations is also feasible. The cost benefit of some of the coconut based cropping systems have been presented, and the low productivity of coconut observed in majority of the coconut growing countries discussed keeping in view the remedial. measures that can be thought of for the existing maladies.